Addressing a few misleading concepts in physics - Bhattacharjee, Pramode (International Journal of Scientific World, 2018)
This paper is concerned with a few misleading issues which are widespread in scientific literature. With a view to getting rid of the ambiguities present in the traditional literature regarding the said issues, proposed solution to each of those issues has been offered. The author feels that with a view to deepening thought and understanding as well as to upgrade the relevant literature at undergraduate level, it is a high time to consider immediate implementation of the present proposal in regard to the pertinent issues raised in this contribution.